Meningkatkan Ketaqwaan Mahasiswa Geografi Melalui Pembinaan Majelis Taklim Berbasis Karakter Islami - Helmi, Dewilna; Paisal Ansiska (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of holding these mentoring sessions is to enrich the spiritual dimension of geography students by strengthening their faith and piety towards Allah SWT. The primary benefit of this effort is that it can help students overcome various challenges and difficulties encountered in their daily lives. In the context of religion, Majelis Ta'lim activities play a very important role. These activities convey and teach religious principles to participating students. Through Majelis Ta'lim activities, students receive spiritual guidance that helps them develop strong character, integrity, and a deeper understanding of religious values. This service is carried out using lecture and question-and-answer methods, and it is expected to benefit geography students by creating a harmonious environment that supports their academic and spiritual development.